Cerebral abnormalities in Friedreich ataxia: A review. (January 2018) - Selvadurai, Louisa P.; Harding, Ian H.; Corben, Louise A.; Georgiou-Karistianis, Nellie
Highlights: Cerebral and cerebellar-cerebral abnormalities are evident in FRDA. Aberrations are observed across white-matter, grey-matter and functional measures. Some evidence indicates cerebello-cerebral disconnectivity and neural compensation. We propose potential mechanisms of cerebral abnormalities. Larger-scale, multi-modal studies are needed to maximise future research impact. Abstract: Friedreich ataxia (FRDA) is an inherited degenerative disorder affecting multiple systems of the body and resulting in symptoms which include progressive ataxia, dysarthria, and cardiomyopathy. Central nervous system pathology has been traditionally ascribed to the spinal cord and dentate nucleus of the cerebellum. However, cerebral abnormalities in FRDA are being increasingly documented via multiple neuroimaging techniques. Understanding the nature and implications of cerebral abnormalities in FRDA provides more comprehensive knowledge of nervous system involvement in this disorder and increases the prospects of identifying effective treatment targets. We review the cerebellar and the cerebral involvement with a focus on the emerging in vivo human neuroimaging findings suggesting wide-spread cerebral involvement, including aberrant cerebellar-cerebral connectivity. We synthesise the findings by proposing potential mechanisms that may drive these effects. Finally, we identify future research directions which, we argue, will lead to a better understanding of the extent and potential mechanisms of cerebral aberrations in FRDA.